A Comparison of Frequency Domain Block MIMO Transmission Systems - Kalbasi, Reza (2018)
Block transmission techniques, with appropriate cyclic prefix and frequency-domain processing schemes, have been shown to be excellent candidates for digital transmission over severely time-dispersive channels, allowing good performance with implementation complexity that is much lower than traditional time-domain processing schemes. Orthogonal frequencydivision multiplexing (OFDM) modulation is the most popular block transmission technique. Single-carrier (SC) modulation using frequency-domain equalization (FDE) is an attractive alternative approach based on this principle. In this paper, we propose two new receiver structures for multiple-input–multiple-output (MIMO) channels employing SC (MIMO-SC) modulation and FDE schemes. These receivers have a hybrid structure with frequency-domain feedforward and time-domain feedback filters for intersymbol interference (ISI) and interference cancellation. The proposed schemes are compared with different MIMO systems employing OFDM modulation (MIMO-OFDM) receivers in terms of performance [bit error rate (BER) and throughput] and complexity. Our performance results show the superiority of MIMO-SC approaches relative to MIMO-OFDM in terms of the BER performance for the simulated scenarios. Also, the simulation results show that the proposed hybrid MIMO-SC receivers yield a higher throughput than a MIMO-OFDM system